2021
DOI: 10.52711/0974-360x.2021.00790
|View full text |Cite
|
Sign up to set email alerts
|

Standardization and Phytochemical screening of Carica papaya seeds

Abstract: The present work focus to evaluate the physicochemical and preliminary phytochemical studies on the seeds of family Caricaceae. The plants resources which are used in pharmaceutical formulation standardization was carried out on the basis of organoleptic properties, physical characteristics, and physico-chemical properties. Different Physicochemical parameters ash values, extractive values, loss on drying, foreign matter, fluorescence analysis, and pH were evaluated. Macroscopical characteristics and Physicoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…p53 activation triggers mitochondrial cytochrome C , which is followed by Caspase-9 and Caspase-3 activation. This is consistent with the findings of Singh et al [ 29 ], who confirmed the increase of p53 gene expression fivefold after being treated with papaya seed extract and down-regulation of the Bcl-2 gene. Additionally, Hussar et al [ 30 ] stated that the development of the apoptosome, a protein complex contributes to the conversion of pro -Caspase-9 into active Caspase-9 , which then activates procaspase-3 to accelerate apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…p53 activation triggers mitochondrial cytochrome C , which is followed by Caspase-9 and Caspase-3 activation. This is consistent with the findings of Singh et al [ 29 ], who confirmed the increase of p53 gene expression fivefold after being treated with papaya seed extract and down-regulation of the Bcl-2 gene. Additionally, Hussar et al [ 30 ] stated that the development of the apoptosome, a protein complex contributes to the conversion of pro -Caspase-9 into active Caspase-9 , which then activates procaspase-3 to accelerate apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…There are similarities between these findings and our results. Additionally, the methanolic extract of C. papaya activity against fungi supports evidence from clinical observations ( Singh and Ali, 2012 ; Nilofer and Chenthamarai, 2021 ). During the first week of the experiment, Itraconazole, employed as a control for treating M. canis , showed a wide area of inhibition.…”
Section: Discussionsupporting
confidence: 75%
“…The inhibition activity was more important for fungi (16.5 to 60 mm) than bacteria (10 to 20 mm). Antimicrobial activities of papaya seeds essential oils was also previously proved (Tapsoba and Deschamps, 2006;Singh and Ali, 2011;Muhamad et al, 2017;Zhang and Chen, 2017;Seshamamba et al, 2018;Heena and Sunil, 2019;Chai et al, 2020;Dotto and Abihudi, 2021;Li et al, 2021;Yi et al, 2022). The inhibition diameter for all Candida strains is higher than those of all commercial antibiotics and also higher than those found by He et al (2017) which was less than 34 mm.…”
Section: Discussionmentioning
confidence: 64%
“…Polyphenols are secondary metabolites compounds widely distributed in plants, where they perform various functions related to growth, reproduction and protection against pathogens, predators, diseases, and UV radiation (Aguilar-Veloz et al, 2020). The polyphenol content as well as the other phytochemicals have some antimicrobial activities (Singh and Ali, 2011;Yanty et al, 2014;Igwe, 2015;Salla et al, 2016;He et al, 2017;Zhang and Chen, 2017;Tan, 2019;Othman et al, 2019;Manso et al, 2021). The antimicrobial activity of papaya seeds essential oils is then tributed to the phytochemicals compound.…”
Section: Discussionmentioning
confidence: 99%